Criterion scores, construct validity and reliability of a web-based instrument to assess physiotherapists' clinical reasoning focused on behaviour change: ‘Reasoning 4 Change’ - Elvén, Maria (AIMS Public Health, 2018)
Background and aim: ‘Reasoning 4 Change’ (R4C) is a newly developed instrument, including four domains (D1–D4), to assess clinical practitioners' and students' clinical reasoning with a focus on clients' behaviour change in a physiotherapy context. To establish its use in education and research, its psychometric properties needed to be evaluated. The aim of the study was to generate criterion scores and evaluate the reliability and construct validity of a web-based version of the R4C instrument. Methods: Fourteen physiotherapy experts and 39 final-year physiotherapy students completed the R4C instrument and the Pain Attitudes and Beliefs Scale for Physiotherapists (PABS-PT). Twelve experts and 17 students completed the R4C instrument on a second occasion. The R4C instrument was evaluated with regard to: internal consistency (five subscales of D1); test-retest reliability (D1–D4); inter-rater reliability (D2–D4); and construct validity in terms of convergent validity (D1.4, D2, D4). Criterion scores were generated based on the experts' responses to identify the scores of qualified practitioners' clinical reasoning abilities. Results: For the expert and student samples, the analyses demonstrated satisfactory internal consistency (α range: 0.67–0.91), satisfactory test-retest reliability (ICC range: 0.46–0.94) except for D3 for the experts and D4 for the students. The inter-rater reliability demonstrated excellent agreement within the expert group (ICC range: 0.94–1.0). The correlations between the R4C instrument and PABS-PT (r range: 0.06–0.76) supported acceptable construct validity. Conclusions: The web-based R4C instrument shows satisfactory psychometric properties and could be useful in education and research. The use of the instrument may contribute to a deeper understanding of physiotherapists' and students' clinical reasoning, valuable for curriculum development and improvements of competencies in clinical reasoning related to clients' behavioural change.